If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30 = -14 + n Solving -30 = -14 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -30 + -1n = -14 + n + -1n Combine like terms: n + -1n = 0 -30 + -1n = -14 + 0 -30 + -1n = -14 Add '30' to each side of the equation. -30 + 30 + -1n = -14 + 30 Combine like terms: -30 + 30 = 0 0 + -1n = -14 + 30 -1n = -14 + 30 Combine like terms: -14 + 30 = 16 -1n = 16 Divide each side by '-1'. n = -16 Simplifying n = -16
| 5(3-2m)+5m=65 | | 30s-30=29s | | 216+12w=312+4w | | N-24=6m | | 24-x=7(x+8) | | z/12=10 | | 6(4x-(7-7y+2x)+7y)= | | 2(-18+13)=-10 | | sine(5x)=0 | | c=0.6p^2-7.2p+48 | | 2n^2=(-144) | | -15+9x+15y=0 | | 8d+9-10d=13 | | 5(w-7)=-5 | | In(x)+In(3)=0 | | (4x+5)(3x-1)= | | 7k-2(k+6)=(-2) | | 17x-y=40 | | X+(5x-5)+(5x-5)=155 | | 11(4-6y)+5(13x+1)=9 | | Q+-4=r | | 26+5*26=-10+6*26+10 | | 4(10-x)=-7x+7 | | 4y-12=68 | | 4x-5=4x-2 | | 3x+2x+3=-x+5 | | C-11=d | | 7k-6-2k=1 | | 1(-6x-6y)=1(0) | | 2(x+13)=-10 | | 6*a+4=-11 | | 7x-3(2x+1)=8x+5+9x-19 |